IBS installation use “stell mould forwork and pre-cast beam and half slab” / Muhamad Azmi Che Anuar - Che Anuar, Muhamad Azmi (Universiti Teknologi Mara, Perak, 2014)
Practical training is a course that should be completed by all students who took the final semester of Diploma in Building Surveying. Students can choose where company or palace to conduct the practical training. I have selected the state government departments of the NUKIMA Sdn Bhd. as a place for the practical training. I have placed at site office Additional Block Hospital Jeli. The project manager as a leader in this site had been appointed to be my supervisor during the training. During the practical training, I learned about the method of installation for use steel mould formwork and precast element in building construction. For example, I am know how the method installation for both of construction and I also know how to make inspection the building use the IBS method construction on this building. Practical training will be end after four months the students complete the training. Finally, students will then prepare a report according to the topics that relevant to the work during the practical training that had been done.